Cellular immune response after vaccination in patients with cance: review on past and present experiences - Rüthrich, Maria Madeleine; Giesen, Nicola; Mellinghoff, Sibylle Christiane; Rieger, Christina; Lilienfeld-Toal, Marie von (Vaccines, 2022)
Patients with cancer are at particular risk for infection but also have diminished vaccine responses, usually quantified by the level of specific antibodies. Nonetheless, vaccines are specifically recommended in this vulnerable patient group. Here, we discuss the cellular part of the vaccine response in patients with cancer. We summarize the experience with vaccines prior to and during the SARS-CoV-2 pandemic in different subgroups, and we discuss why, especially in patients with cancer, T cells may be the more reliable correlate of protection. Finally, we provide a brief outlook on options to improve the cellular response to vaccines.